2007
DOI: 10.1021/bm0701503
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Egg-Box-Compatible Interactions in Calcium−Alginate Gels from Fiber X-ray Diffraction

Abstract: The structures of guluronic-acid-rich alginate in the acid and calcium forms were investigated using fiber X-ray diffraction. Data recorded for alginate fibers in the acid form show a repeat along the chain axis of c = 0.87 nm, a value that is in agreement with the one measured by Atkins et al. (Biopolymers 1973, 12, 1865) and contradicts a repeat of 0.78 nm recently suggested by Li et al. (Biomacromolecules 2007, 8, 464). In the Ca2+ form, our observations indicate that the junction zone involves dimerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
246
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(256 citation statements)
references
References 21 publications
6
246
1
3
Order By: Relevance
“…The formation of a matrix of alginate and divalent cations such as Ca 2ϩ has been widely studied (36,41,48). Such a matrix is known as an "egg-box" formation of alginate-Ca.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a matrix of alginate and divalent cations such as Ca 2ϩ has been widely studied (36,41,48). Such a matrix is known as an "egg-box" formation of alginate-Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium, a divalent ion with two positive charges, interacts with alginate linear chains to form a cross-linked hydrogel (28). This mechanism of cross-linking has been studied and been reported elsewhere (23).…”
Section: Preparation Of the Swellable Ciprofloxacin-loaded Nano-in-mimentioning
confidence: 90%
“…The anionic alginate interacts with cationic chitosan (24), which is biocompatible and biodegradable polysaccharide (25) and is capable to prolonged drug release (26). In biomedical applications, alginate has been extensively investigated due to its unique ability to form hydrogel via ionotropic crosslinking with divalent cations such as Ca 2+ (27,28). However, it has been recently reported that calcium in alginate hydrogel stimulates an inflammatory response (29), which is undesirable in lungs for most therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The bead-effect becomes more intense as the amount of the gold anions becomes higher, indicating that the presence of gold anions affects the electrospinning, although the changes that the gold anions induce to the conductivity and surface tension of the solutions (see Table 1 on the G units. Even more, as it is well described by the egg-box model [30], [31], through an inter-chain dimerization, alginate creates cavities suitable for strong binding with anions. We believe that this kind of linkage between two or more alginate chains is the main reason for the bead-effect, since the new arrangement brings more alginate chains together and destroys their entanglement with the PEO chains.…”
Section: Spinnability Versus Concentration Of Gold Anionsmentioning
confidence: 99%